2021
DOI: 10.1136/bjsports-2021-105030
|View full text |Cite
|
Sign up to set email alerts
|

Is early activity resumption after paediatric concussion safe and does it reduce symptom burden at 2 weeks post injury? The Pediatric Concussion Assessment of Rest and Exertion (PedCARE) multicentre randomised clinical trial

Abstract: ObjectiveInvestigate whether resuming physical activity (PA) at 72 hours post concussion is safe and reduces symptoms at 2 weeks, compared with resting until asymptomatic.MethodsReal-life conditions, multicentre, single-blinded randomised clinical trial, conducted in three Canadian paediatric emergency departments (ED). Children/youth aged 10–<18 years with acute concussion were recruited between March 2017 and December 2019, and randomly assigned to a 4-week stepwise return-to-PA protocol at 72 hours post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
1
37
1
2
Order By: Relevance
“…The SAEP group received two in-person supervised sessions as well as remote supervision and reminders for exercise. These sessions may have accounted for some of the differences between groups by increasing the confidence of study participants in their treatment prescription or ensuring adherence to study procedures [ 47 ]. However, participants in both groups had access to interventions, academic accommodations, physical therapy, and pharmacological options associated with sleep, headache, or affective issues, consistent with current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The SAEP group received two in-person supervised sessions as well as remote supervision and reminders for exercise. These sessions may have accounted for some of the differences between groups by increasing the confidence of study participants in their treatment prescription or ensuring adherence to study procedures [ 47 ]. However, participants in both groups had access to interventions, academic accommodations, physical therapy, and pharmacological options associated with sleep, headache, or affective issues, consistent with current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although the PedCARE trial randomized concussion participants to either resume non-contact, aerobic physical activity at 72 h post-concussion or rest until asymptomatic, the concussion participants were regrouped and the randomization was broken for the purposes of this study as both groups completed similar levels of physical activity ( Ledoux et al, 2021 ). The study herein is a cross sectional design of the data collected for PedCARE +MRI .…”
Section: Methodsmentioning
confidence: 99%
“…Sex was also covaried as reduced connectivity post-concussion was recently identified in females within and between multiple regions ( Shafi et al, 2020 ). To account for the possibility of group differences between the physical activity and rest concussion groups [despite no significant activity level differences ( Ledoux et al, 2021 )], assigned groups were added as covariates. For the purposes of this analysis, each participant was assigned a composite diagnostic score that was the sum of: 1 point per prior diagnosis of ADHD, anxiety, depression or learning disability; and total number of previous concussions.…”
Section: Methodsmentioning
confidence: 99%
“…This study is a planned secondary analysis of a randomized clinical trial (RCT) completed at CHEO from May 2018 to February 2020 called Pediatric Concussion Assessment of Rest and Exertion+MRI (PedCARE +MRI ), which was an adjunct study to Pediatric Concussion Assessment of Rest and Exertion (PedCARE) Ledoux et al, 2022). The primary objective of the PedCARE +MRI study was to investigate whether early resumption of physical activity at 72 hours post-concussion would lead to improved neurophysiological outcomes.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Although the parent study was an RCT, for this study the physical activity and rest until asymptomatic groups were combined, since it was previously found that the groups had similar patterns of physical activity (Ledoux et al, 2022). Recruitment took place through CHEO's Emergency Department.…”
Section: Study Design and Settingmentioning
confidence: 99%